Planung, Kollektive und Kulturen - Akteursperspektiven in der Planungskultur. - Wolff, Almut (Routledge, 2016)
Die Autorin fundiert die theoretischen Wurzeln des Planungskultur-Ansatzes mithilfe eines seit kurzem in den Kulturwissenschaften diskutierten, innovativen Kulturbegriffs, der sich an Kollektiven und diversen Akteursperspektiven orientiert und dessen Charakteristika sich aus Differenzen ableiten lassen. Sie stellt dar, welche Folgerungen dies für das Verständnis von Planungskultur-Ansätzen impliziert und welche Perspektiven sich für die Forschung ergeben.

The term planning culture is applied both in the sense of an analytical approach as well as in the sense of a normative concept for cooperative planning processes. In its implicit meaning the term always implies a notion of the plurality of the involved actors. Nevertheless, research on planning cultures aims to describe homogeneous cultural entities - on national or regional levels. This article examines whether, in point of fact, planning cultures are constituted by the complexity of interactions among the involved actors. Recent research approaches question the traditional concept of homogeneous cultures and are evolving toward a concept of poly-collective cultures. This leads toward a notion of culture that provides the individual person with multiple affiliations to collectives and cultures. Following this model, culture is generated through interaction. This text explores if this differentiation of actors within a culture is adoptable as a research approach for planning cultural research.
Planning, collectives and cultures - Actor perspectives in planning culture.
Keywords: Stadtplanung; Planungsprozess; Planungstheorie; Sozialverhalten; Planungskultur; Kulturbegriff; Kulturwissenschaft; Handlungstheorie; Planungsforschung; Forschungsansatz; Kollektiv; Akteur